Sonic Seasoning and Other Multisensory Influences on the Coffee Drinking Experience - Spence, Charles (Frontiers in Computer Science, 2021)
The coffee drinking experience undoubtedly depends greatly on the quality of the coffee bean and the method of preparation. However, beyond the product-intrinsic qualities of the beverage itself, there are also a host of other product-extrinsic factors that have been shown to influence the coffee-drinking experience. This review summarizes the influence of everything from the multisensory atmosphere through to the sound of coffee preparation, and from the typeface on the coffee packaging through the drinking vessel on the coffee drinking experience. Furthermore, the emerging science around sonic seasoning, whereby specific pieces of music or soundscapes, either pre-composed or bespoke, are used to bring out specific aspects in the taste (e.g., sweetness or bitterness) or aroma/flavour (nutty, dark chocolate, dried fruit notes, etc.) of a coffee beverage is also discussed in depth. Relevant related research with other complex drinks such as beer and wine are also mentioned where relevant.